Seawater carbonate chemistry and boron incorporation of planktic foraminifer Orbulina universa during experiments, 2011 - Katherine A Allen; Bärbel Hönish; Stephen M Eggins; Jimin Yu; Howard J Spero; Henry Elderfield (PANGAEA, 2011)
Culture experiments with living planktic foraminifers reveal that the ratio of boron to calcium (B/Ca) in Orbulina universa increases from 56 to 92 μmol mol-1 when pH is raised from 7.61 +/- 0.02 to 8.67 +/- 0.03 (total scale). Across this pH range, the abundances of carbonate, bicarbonate, and borate ions also change (+ 530, - 500, and + 170 μmol kg-1, respectively). Thus specific carbonate system control(s) on B/Ca remain unclear, complicating interpretation of paleorecords. B/Ca in cultured O. universa also increases with salinity (55-72 μmol mol-1 from 29.9-35.4 per mil) and seawater boron concentration (62-899 μmol mol-1 from 4-40 ppm B), suggesting that these parameters may need to be taken into account for paleorecords spanning large salinity changes (~ 2 per mil) and for samples grown in seawater whose boron concentration ([B]SW) differs from modern by more than 0.25 ppm. While our results are consistent with the predominant incorporation of the charged borate species B(OH)4 into foraminiferal calcite, the behavior of the partition coefficient KD (defined as [B/Ca]calcite/B(OH)4/HCO3seawater) cannot be explained by borate incorporation alone, and suggests the involvement of other pH-sensitive ions such as CO3 For a given increase in seawater B(OH)4, the corresponding increase in B/Ca is stronger when B(OH)4 is raised by increasing [B]SW than when it is raised by increasing pH. These results suggest that B incorporation controls should be reconsidered. Additional insight is gained from laser-ablation ICP-MS profiles, which reveal variable B/Ca distributions within individual shells.
Supplement to: Allen, KA et al. (2011): Controls on boron incorporation in cultured tests of the planktic foraminifer Orbulina universa. Earth and Planetary Science Letters, 309(3-4), 291-301, https://doi.org/10.1016/j.epsl.2011.07.010